(untitled) (American Journal of Islam and Society, 2014)
On January 15, 2014, Md. Mahmudul Hasan, assistant professor in the Department of English Language and Literature at the International Islamic University Malaysia, addressed an audience at the IIIT headquarters in Herndon, VA. He spoke on how Muslims have tended to associate English studies with western value systems, secularism, and anti-Islamic practices. He opened his talk with some background information. He was educated at a madrassa and then chose to study western (English) literature, much to his father’s disappointment – he firmly believed that his son, whom he had always envisaged as an Islamic scholar, would come out of the university as a secularist, an atheist, or an agnostic. Although this may not be the case today, at his father’s time people could actually see their university-enrolled children undergo some changes or adopt the various western lifestyles uncritically at the expense of their traditional Islamic upbringing. Reflecting further on the context that had given rise to this attitude, Hasan pointed out the tendency at that time, and based solidly upon the Subcontinent’s colonial experience, to associate English literature studies with both colonialism and western Christendom. In response to this, contemporary scholars of postcolonial studies employ the twin strategies of abrogation and appropriation to dismantle the original intent behind introducing English literary studies and, simultaneously, to create platforms of self-assertion and resistance. Those who support the Islamization of English literary studies propose a similar approach to English literature in order to counterbalance the un-Islamic cultural influences as well as to present the Islamic worldviews in relation to the life-worlds that these literary texts are reputed to promote. He said that many Muslims find it difficult to reconcile “Islam” and “English literature,” for how can there be any relationship between them? This is not as illogical as it may seem, however, for the British introduced English literature into the Subcontinent long before they introduced it into the United Kingdom itself. It was offered in the former in 1830, but only ninety years later in the latter. In fact, according to Hasan, the subject itself has a colonial background, for it, along with Christian missionary activity, was designed to ...